Análisis prácticas asociadas a la sostenibilidad en la cadena de valor del turismo en Norte de Santander - Liana Carolina Ovalles-Pabón; Ana Delfina Tovar-Quiroz (Mundo Fesc)
In Norte de Santander, tourism services are grouped based on the type of municipality and the capacity to meet annual user demand. This analysis applied a tool to 322 tourism establishments, comprising 45 accommodation providers, 131 bars and restaurants, 8 tour guide companies, and 19 travel agencies; each with national tourism registration in the respective Chambers of Commerce of Cúcuta and Pamplona. This tool collected information related to the support activities that generate value for the organization according to Porter's value chain, directly related to environmental, social, and economic components. This analysis identified that, at the infrastructure level, providers of accommodation and gastronomy services in Cúcuta and Pamplona present more than 50% difficulties in adopting sustainable strategies in processes related to adapting space for different disabilities, managing water resources, saving energy, and developing location improvements. In human resources-related activities, it was identified that more than 60% of providers do not speak a second language in customer service. Similarly, in activities related to the development or implementation of technology, it was specifically identified in Pamplona that 80% of accommodation, guidance, and transportation service providers struggle with the use of specific software for the service they provide, the development of studies on technological changes in competition, the establishment of automated processes, and cybersecurity. For PSTs, addressing environmental and social processes in relation to the economic component ends up becoming an additional expense or situations that cannot be controlled. Promoting sustainable development in tourism requires support in technological updating processes, strengthening human capital, and linking production processes.